If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 5 = 41 Reorder the terms: 5 + 12x = 41 Solving 5 + 12x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 12x = 41 + -5 Combine like terms: 5 + -5 = 0 0 + 12x = 41 + -5 12x = 41 + -5 Combine like terms: 41 + -5 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| 6x+5=35 | | 4x-3=2x+9 | | 3x+y=4 | | 9x-2y=3 | | 31-12x=211 | | 14x-32=234 | | 5x+17=-38 | | 12x-32=112 | | 8x+11=-37 | | -11x-20=-97 | | -5x+11=41 | | 3x+5=26 | | 17-x=4 | | 2x+33=17 | | -2x-5=7 | | -3x-7=-28 | | 2x=4+x | | 3x=x+4 | | x+4=2x+3 | | 3x=30 | | 10+4x=18+3x | | 10+3x=18+3x | | 14-4(2k+4)=-2(4-3k) | | 9a+3=6a+6 | | 2a+20-4a=10 | | 2x+4=x+10 | | 21x-3=4 | | -x-21=6 | | 12=-14x+5 | | 8.1+3.8h-5.6h=-7.2 | | 8.1+3.8h-5.6h=7.2 | | 2(4s-16)-5s=-5 |